Prevalence of Depression and Its Associated Factors among Adult Libyan Diabetic Patients Attending Golden Polyclinic, Al-Badri, Tripoli - Ehmeid Khalifa; Munira Alduwaik; Aisha Benrween (Khalij-Libya Journal of Dental and Medical Research, 2024)
Background and aims: Depression is a significant public health concern and a common comorbid condition among patients with diabetes mellitus. This study aims to assess the prevalence of depression and its associated factors among patients with diabetes in the Al-Badri polyclinic. Methods: A descriptive cross-sectional study was conducted at Al-Badri Polyclinic from February to April 2024. The presence of depression among diabetes patients was assessed using the 9-item Patient Health Questionnaire (PHQ-9) scale. Data was entered and analyzed by using SPSS software version 26. Results: A total of two hundred and forty-seven participants were enrolled in the study, with 142 (57.5%) being female and 168 (68.0%) aged between 41 and 60 years. The majority of participants (71.7%) were married, and 40.5% were employed. Additionally, 78% had a positive family history of diabetes mellitus. Among the participants, 43.3% were smokers. The duration of diabetes mellitus was more than 10 years for 52.2% of the patients. Approximately two-thirds of the patients (61.5%) were taking tablets for the treatment of DM. The majoring of the patients (98.8%) had an HbA1c level of 6.5 or higher. Approximately one-third of the patients had hypertension as a comorbidity with DM, and 12.1% had heart disease as a complication of diabetes. The overall prevalence of moderate depression among the diabetes patients at the clinic was 24.7%. The majority (70.4%) exhibited mild depression, and 4.9% experienced minimal depression. No cases of severe depression were identified. Factors independently associated with depression included being on age, marital status, insulin therapy, and comorbidities. Conclusion: Depression was prevalent in our diabetic patients. Factors independently associated with this included being on age, marital status, insulin therapy, and comorbidities. The study emphasizes and recommends the importance of identifying and managing depression among diabetes patients. It is also recommended to increase awareness of the benefits of early diagnosis of patients to prevent major forms of depression and cost saving for the health system. Programs for screening depression should be implemented in primary care settings. خلفية وأهداف الدراسة: يعد الاكتئاب من المشاكل الصحية العامة الكبيرة كما يعتبر من الامراض الشائعة بين مرضى داء السكري. تهدف هذه الدراسة إلى تقييم معدل انتشار الاكتئاب وتحديد العوامل المرتبطة به بين مرضى السكري في عيادات مجمع البدري. منهجية الدراسة: أجريت هذه الدراسة الوصفية المقطعية في عيادات مجمع البدري والتي امتدت من شهر فبراير إلى غاية أبريل 2024، كما تم تقييم حالات الاكتئاب بين مرضى السكري باستخدام استبيان PHQ-9 والذي يضم 9 بنود. استخدم برنامج SPSS اصدار 26 في إدخال البيانات وتحليلها. النتائج: شارك في الدراسة 247 من ضمنهم 142 (57.5%) إناث كان فيهم 168 (68%) اعمارهم تتراوح بين 41 و 60 عاماً. غالبية المشاركين في الدراسة كانوا متزوجين (71.7%) وكان منهم 40.5% لديهم اشغال يعملونها. التاريخ العائلي لمرض السكري كان موجود بين 78% منهم. ما نسبته 43.3% من المشاركين في الدراسة كانوا مدخنين. الفترة الزمنية لمرض السكري بين هؤلاء المرضى 52.2% كانت تزيد على 10 سنوات. ثلث المرضى 61.5% كانوا يتلقون أقراصاً لعلاج مرض السكري وكان التحليل التراكمي للسكر لغالبية المرضى 98.8% عند مستوى 6.5 أو ازيد من ذلك. يعاني ثلثي المرضى من ارتفاع ضغط الدم كمرض مصاحب لداء السكري، كما كان 12.1% منهم يعانون من امراض القلب بسبب مضاعفات السكري. بلغ معدل انتشار الاكتئاب ذو المستوى المعتدل 24.7%، بينما معدل الاكتئاب الخفيف 70.4% والبسيط كان 4.9%. لم يتم تحديد اي حالات اكتئاب حاد. تشمل العوامل المرتبطة بشكل مستقل بالاكتئاب التقدم في السن والحالة الاجتماعية وعلاج الانسولين والامراض المصاحبة. الاستنتاج: اشارت الدراسة إلى ان الاكتئاب منتشراً بين مرضى السكري في هذه الدراسة. من بين العوامل المرتبطة بشكل مستقل هي العمر والحالة الاجتماعية وعلاج الانسولين والامراض المصاحبة. تؤكد الدراسة وتوصي بأهمية تحديد الاكتئاب ومعالجته بين مرضى السكري. كما توصي بزيادة الوعي بفوائد التشخيص المبكر للمرضى للوقاية من أشكال الاكتئاب الرئيسية وتوفير الامكانيات لتقديم الرعاية الصحية وتنفيذ برامج فحص الاكتئاب في مراكز الرعاية الأولية